ANALISIS GAYA MENGAJAR GURU PENDIDIKAN AGAMA KRISTEN DI SD NEGERI 116894 KUALA BERINGIN KABUPATEN LABUHAN BATU UTARA TAHUN PEMBELAJARAN 2017/2018 - Eva Sari Ayu Pardosi (IAKN Tarutung, 2018)
Abstract, The research aims to know of percentage the teaching style of teachers learning Christian education in SD Negeri 116894 Kaula Beringin Labuhan, Batu Utara regency in 2017/2018 academic years. The hypothesis of this research was teaching style of teachers learning Christian education in SD Negeri 116894 Kaula Beringin Labuhan in 2017/2018 academic years 60% of the expected, with 40 of research samples. Research instrument in the form of a closed questionnaire prepared by the researchers, with a total of 24 items compiled based on theoretical indicators and tested for validity and reliability. Analyzing data was indicated thatthe teaching style of teachers learning Christian education in SD Negeri 116894 Kaula Beringin Labuhan by 79.84% with the calculation by comparing tcountttable namely 16.6231.684. The conclusion drawn from this study was the teaching style of teachers learning Christian education in SD Negeri 116894 Kaula Beringin Labuhan, Batu Utara regency in 2017/2018.